2015
DOI: 10.1016/j.jfluidstructs.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Flapping dynamics of an inverted flag in a uniform flow

Abstract: a b s t r a c tThe flapping motions of an inverted flag in a uniform flow were simulated using the immersed boundary method. The strain energy of the inverted flag was used as an indicator of the energy harvesting system efficiency. The flapping dynamics of and vortical structures around the inverted flag were examined in terms of the bending rigidity (γ) and the Reynolds number (Re). Three flapping motion modes were observed: a deflected mode, a flapping mode, and a straight mode. A mode intermediate between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 20 publications
9
51
0
Order By: Relevance
“…These biological structures are also very narrow, which further restricts flapping. Indeed, elimination of inverted flag flapping at low Reynolds numbers is observed in recent computational simulations (Ryu et al 2015).…”
Section: Relation To the Flapping Of Biological Structuresmentioning
confidence: 72%
See 3 more Smart Citations
“…These biological structures are also very narrow, which further restricts flapping. Indeed, elimination of inverted flag flapping at low Reynolds numbers is observed in recent computational simulations (Ryu et al 2015).…”
Section: Relation To the Flapping Of Biological Structuresmentioning
confidence: 72%
“…This quantitative behaviour of the Strouhal number with increasing flow speed, and its insensitivity to Reynolds number, are identical to observations of VIVs of a broad range of mechanical structures; see § 4.1.2. The low Reynolds number computational simulations of inverted flag flapping by Ryu et al (2015) exhibit similar behaviour, even though the Reynolds numbers are two orders of magnitude smaller.…”
Section: Strouhal Number Of Flappingmentioning
confidence: 75%
See 2 more Smart Citations
“…Figures 1a and 1b show a single measurement of such an inverted leaf (taken from Sader et al (2016a)) where largeamplitude flapping (limit cycle behaviour) is evident. Detailed studies of the related and canonical 'inverted flag' configuration-a cantilevered elastic sheet oriented such that the flow impinges on its free edge with its clamp downstream-provide an explanation for this leaf behaviour and show that orientation of the flag can have a dramatic effect (Kim et al 2013;Cossé et al 2014;Tang et al 2015;Ryu et al 2015;Sader et al 2016a). Kim et al (2013) reported the first detailed measurements on the stability and dynamics of the inverted flag, in both air and water.…”
Section: Introductionmentioning
confidence: 99%